Magneto-acceleration of Ostwald ripening in hollow Fe3O4 nanospheres. Issue 33 (29th June 2016) - Ding, Wei; Hu, Lin; Sheng, Zhigao; Dai, Jianming; Zhu, Xuebin; Tang, Xianwu; Hui, Zhenzhen; Sun, Yuping
Abstract : The magnetic field-induced acceleration of the Ostwald ripening process was demonstrated firstly in the formation of hollow Fe3 O4 nanospheres. Abstract : The magnetic field-induced acceleration of the Ostwald ripening process was demonstrated firstly in the formation of hollow Fe3 O4 nanospheres. Similar to the maintaining time, the magnetic field can act as an independent parameter to control the crystallite size, hollow structure, and pore size of nanostructures in the Ostwald ripening process.